Kiblat Magazine in the Field of Anti-Communist Propaganda in Indonesia, 1966–1967 - Hutama, Naufal Tri; Jassin, Suparman; Purnama, Agung (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
This study aims to reconstruct the contribution of Kiblat magazine to anti-communist propaganda during Indonesia's political transition (1966–1967). Drawing upon Harold D. Lasswell's communication model of propaganda—who says what in which channel to whom with what effect—this research reveals how Kiblat served as a vehicle for delegitimizing the Indonesian Communist Party (PKI) and communism at large. The magazine featured narratives contributed by Islamic figures and military actors (who), constructing communism as a direct threat to religion and national integrity (says what). These messages were conveyed through a religious-political media channel (in which channel), citing sources such as the military newspaper Angkatan Bersendjata, and targeted at the broader Muslim population in Indonesia (to whom). The outcome was reinforcing public opinion in favor of anti-communist sentiment and the depoliticization of the PKI (with what effect). This study highlights the strategic function of Islamic media in ideological contests during critical moments of national upheaval. Kiblat did not merely articulate religious values but also shaped political discourse and legitimized the regime. While limited to a specific timeframe and publication, this research opens pathways for further inquiry into the intersection of religion, media, and state power, especially concerning how Islamic media respond to or align with political authority during times of transformation.